2016
DOI: 10.1016/j.neuron.2015.12.034
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 Receptor Differentially Regulates Spontaneous and Evoked Transmission via Mitochondria at Hippocampal Synapses

Abstract: SummaryThe insulin-like growth factor-1 receptor (IGF-1R) signaling is a key regulator of lifespan, growth, and development. While reduced IGF-1R signaling delays aging and Alzheimer’s disease progression, whether and how it regulates information processing at central synapses remains elusive. Here, we show that presynaptic IGF-1Rs are basally active, regulating synaptic vesicle release and short-term plasticity in excitatory hippocampal neurons. Acute IGF-1R blockade or transient knockdown suppresses spike-ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
143
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 74 publications
(96 reference statements)
5
143
3
Order By: Relevance
“…Furthermore, a blockade of IGF-1 reduced the activity of IGF-1R. This implied that a basal IGF-1R activity exist and is activated by intrinsic IGF-1 concentration during hippocampal synaptic function (Adams et al, 2000; Yamaguchi et al, 1990 as cited by Gazit et al, 2016). Since IGF-1R directly mediates the activity of synaptophysin, we investigated the significance of a change in IGF-1R on other presynaptic proteins involved in neurotransmitter synthesis and function.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, a blockade of IGF-1 reduced the activity of IGF-1R. This implied that a basal IGF-1R activity exist and is activated by intrinsic IGF-1 concentration during hippocampal synaptic function (Adams et al, 2000; Yamaguchi et al, 1990 as cited by Gazit et al, 2016). Since IGF-1R directly mediates the activity of synaptophysin, we investigated the significance of a change in IGF-1R on other presynaptic proteins involved in neurotransmitter synthesis and function.…”
Section: Discussionmentioning
confidence: 94%
“…Although our study addressed basic relationship between synaptophysin and IGF-1R expression (Fig. 3I–L), a recent study elaborately showed the role of hippocampal IGF-1R in real-time regulation of synaptic function and presynaptic vesicle release (Gazit et al, 2016). Their results demonstrate that pharmacological inhibition or a genetic knock down of IGF-1R reduced synaptophysin expression, and significantly reduced presynaptic activity.…”
Section: Discussionmentioning
confidence: 98%
“…To measure the functionality of mitochondria under these conditions, we imaged mitochondrial membrane potential via tetramethylrhodamine (TMRM, [14]) and mitochondrial matrix calcium dynamics during action potential (AP) evoked neurotransmitter release using a genetically-encoded, matrix-targeted calcium indicator GCaMP5G (mito-GCaMP5G) [15]. Mitochondrial membrane potential is generated via the proton gradient, resulting from oxidative phosphorylation along the electron transport chain (ETC), across the inner mitochondrial membrane (IMM) which gates ATP generation.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria are the principal producers of cellular energy, and thus are crucial for neuronal function and survival. Mitochondrial ATP production sustains various essential functions at synapses such as: 1) maintaining ion gradients across the cellular membrane, which is required for axonal and synaptic membrane potentials [1]; 2) mobilizing synaptic vesicles from reserve pools to release sites [2]; 3) supporting synaptic vesicle release and recycling [35]; 4) supporting synaptic assembly and plasticity [6, 7]. …”
Section: Introductionmentioning
confidence: 99%